2005
DOI: 10.2111/1551-5028(2005)058[0366:eamddi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Elk and Mule Deer Diets in North-Central New Mexico

Abstract: Botanical composition of mule deer and elk diets in winter, spring, summer, and autumn was studied during 1998 and 1999 on woodland rangeland in north-central New Mexico using microhistological analysis of fecal samples. Our study area had no livestock grazing for 60 years but was moderately grazed by mule deer and elk. Elk and mule deer shared 3 of the top 5 key forage species when diets were pooled across seasons and years. These 3 species were oak (Quercus sp.), ponderosa pine (Pinus ponderosa Dougl.), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Further, studies have shown that bird populations with high migratory diversity tend to be more resilient to environmental change and population declines (Gilroy et al, 2016). The lack of migratory diversity may be one of the reasons why mule deer populations have generally declined in recent decades, while elk populations continue to flourish (Lindzey, Hepworth, Mattson, & Reese, 1997;Sandoval, Holechek, Biggs, Valdez, & VanLeeuwen, 2005). Thus, the spectrum of migratory diversity of large herbivores could range from species or populations that exhibit high rates of switching and low fidelity to routes, to those that do not switch behaviours and show strong fidelity to routes.…”
Section: Plasticity Of Migratory Behaviour Including Decisions Aboutmentioning
confidence: 99%
“…Further, studies have shown that bird populations with high migratory diversity tend to be more resilient to environmental change and population declines (Gilroy et al, 2016). The lack of migratory diversity may be one of the reasons why mule deer populations have generally declined in recent decades, while elk populations continue to flourish (Lindzey, Hepworth, Mattson, & Reese, 1997;Sandoval, Holechek, Biggs, Valdez, & VanLeeuwen, 2005). Thus, the spectrum of migratory diversity of large herbivores could range from species or populations that exhibit high rates of switching and low fidelity to routes, to those that do not switch behaviours and show strong fidelity to routes.…”
Section: Plasticity Of Migratory Behaviour Including Decisions Aboutmentioning
confidence: 99%
“…Many animals, such as deer and elk, rely on shrub production for a substantial part of their dietary needs. In central New Mexico, shrubs made up 32-61% of elk diets and 60-78% of deer diets in woodland habitats depending on the season (Sandoval et al, 2005). Although, we did not measure ungulate use of shrubs, ungulate use can be a limiting factor facing shrub regeneration and growth.…”
Section: Shrubsmentioning
confidence: 99%
“…However, as a treated area ages, fewer herbaceous forages become available during the growing season, which could potentially account for the avoidance of older treatments during summer. Transitioning into the winter season, deer predominately forage on nearly all browse species (Sowell et al 1985, Sandoval et al 2005), which is more abundant in older treated areas thus mirroring the increased odds of mule deer selection for 4‐year‐old treatments during winter.…”
Section: Discussionmentioning
confidence: 99%